‘Invisible Victims’: Marital Rape – A Curse to Indian Women - Thakur, Kiran; Diwan, Promil (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Marital rape remains one of the most neglected forms of sexual violence in India, despite being recognized internationally as a violation of human rights and gender equality. The Bhartiya Nyaya Sanhita (BNS) continues to exempt husbands from prosecution for rape unless the wife is under eighteen years of age, effectively denying married women equal legal protection. Rooted in patriarchal traditions, this exemption perpetuates the notion of irrevocable consent within marriage and reinforces systemic gender inequality. Comparative perspectives show that while many countries have criminalized marital rape, India continues to treat it primarily as a social issue rather than a legal one. Constitutional guarantees under Articles 14 and 21 highlight the incompatibility of the marital rape exception with fundamental rights. Legislative reform is urgently needed to criminalize marital rape, ensure penalties equal to other forms of rape, and uphold women’s dignity, autonomy, and constitutional rights.